Kepemimpinan Pendidikan yang Efektif: Berlandaskan Agama, Filsafat, Psikologi dan Sosiologi - Abdul Waidl; Sofyan Sauri; Faiz Karim Fatkhullah (Universitas Islam Bunga Bangsa Cirebon, 2021)
How should educational institutions be mobilized? Why does an educational leadership exist? What kind of educational leadership model is needed so that educational institutions can run well, effectively, efficiently and achieve targets. Is a leadership that is closer to change (dynamics) and respects every difference. Or a leadership that is closer to uniformity and discrimination. The following article answers through 4 foundations, namely religion, philosophy, psychology and sociology.